Machine Learning and Student’s Educational Trajectory Mathematical Modelling - Krupa, Tatiana V. (The journal of contemporary issues in business and government, 2021)
The purpose of the article is to describe stages of variables formation and identification and develop a student’s educational trajectory mathematical model and to create a technological model for the application of machine learning methods to predict the optimal educational trajectory of the student. External variables are analyzed, variables’ numerical values are determined, types of collecting information sessions are highlighted. Data arrays from information sources electronic diary Diary.ru and the GlobalLab online platform were analyzed. A mathematical model of the student is presented based on variables. Using the technical and scientific results of the Project will provide useful economic, technological and technical effects.